Effect of Concrete-Representational-Abstract and Explicit Instructional Strategies on Senior Secondary School Students’ Achievement in and Attitude to Mathematics (2013)
Mathematics is viewed as the basis for science and technology as well as a tool for achieving scientific and technological development. Despite the importance to human activities and development, students generally view Mathematics as being an abstract subject. This has resulted in poor performance in the subject arising from the poor instructional strategies adopted in its teaching. Many studies attempting to find a solution to this problem but only a few had focused on such strategies that involve active participation of students in learning through cutting and modeling of the concepts and mastery at every step. This study, therefore, examined the effect of Concrete-Representational-Abstract Instructional Strategy (CRAIS) and Explicit Instructional Strategy (EIS) on students‟ achievement in and attitude to Mathematics. It also investigated the moderating effects of Mathematics learning difficulty and gender on dependent variables. The study adopted the pretest-posttest, control group, quasi experimental design with a 3x3x2 factorial matrix. Two hundred and seventy-nine senior secondary II students from six public schools purposively selected from three local government areas in Ibadan municipality were randomly grouped into two experimental groups and a control group. The experimental groups were exposed to CRAIS and EIS while the control group was exposed to Modified Conventional Teaching strategy for six weeks. Instruments used were: Test on Students Mathematics Learning Difficulties (r = 0.85); Students Mathematics Achievement Test (r = 0.83) and Students Mathematics Attitude Questionnaire (r = 0.79). Three instructional guides on Concrete-Representational– Abstract Instructional Strategy, Explicit Instructional Strategy and Modified Conventional Teaching Strategy were also used. Seven hypotheses were tested at 0.05 significance level. Data were subjected to Analysis of Covariance and Scheffe Post hoc test. Treatment had significant main effect on students achievement in Mathematics (F(2, 260) = 86.4; p<.05). Students taught with the CRAIS had higher achievement (x= 25.1) than those in the control group (x= 19.8) and EIS group ( x = 18.4). There was a significant effect of treatment on students‟ attitude to Mathematics (F (2, 260) = 11.6; p<.05). The CRAIS group had higher attitude (x = 99.0) than the EIS group ( x = 96.6) and control group ( x = 93.5). This shows that CRAIS was effective in enhancing the achievement while CRAIS and EIS were found to be more effective at improving students attitude towards Mathematics. Mathematics Learning Difficulty (MLD) has significant effect on students‟ achievement in Mathematics. (F(2, 260) = 139.1; p<.05). Students with low MLD had higher achievement ( x = 25.8) than their moderate ( x = 17.8) and high MLD ( x = 14.3) counterparts. Also, there was a significant effect of MLD on attitudes to Mathematics (F(2, 260) = 20.2; p<.05). Students with low MLD had higher attitude ( x = 99.5) than their moderate ( x = 95.2) and the high MLD group ( x = 89.3). Gender has no significant effect on students‟ achievement and attitude to Mathematics. Further, there was significant interaction effect of treatment and MLD on achievement in Mathematics (F(4, 260) = 9.3; p<.05). Among students in the CRAIS group, those with low MLD had higher achievement ( x = 31.9) than the moderate ( x = 21.3) and the high MLD ( x = 12.4) respectively.Concrete-Representational-Abstract Instructional Strategy enhanced students‟ achievement in Mathematics whereas both CRAIS and EIS improved their attitude to the subject. Therefore, CRAIS and EIS should be adopted for the teaching of Mathematics. Senior secondary school students should be screened for Mathematics learning difficulties while training programmes on the use of CRAIS and EIS should be organised for Mathematics teachers.